OpEd: Death, economy, and the problem of excess - Roi Livne (economic sociology_the european electronic newsletter, 2020)
Open nearly every book about the US healthcare system and the problem of excess would echo throughout. Healthcare accounts for some 18 percent of US gross domestic product, and the figure continues to rise. Pharmaceutical companies, medical device producers, insurers, hospitals, clinics, laboratories, and physician groups make up a profitable industry that develops, sells, and utilizes ever-more-advanced and expensive methods to diagnose and treat disease. Procedures that only two decades ago were deemed 'extraordinary' are now being used as ordinary treatments, which physicians offer and insurers cover even when their benefit is minimal (Kaufman 2015). It is mind-boggling, indeed, that in a country where so many lack even the most basic access to medical services, many others face a persistent problem of too much.
Keywords: 300